Self Regulated Learning Mahasiswa pada Mata Kuliah Akuntansi Manajemen dan Biaya - T. Tutut Widiastuti A; Tika Karlina Rachmawati; Widiawati Widiawati (Jurnal Maps (Manajemen Perbankan Syariah), 2023)
This research is to see the description of Self regulated learning Students of the Faculty of Islamic Economics and Business UIN Sunan Gunung Djati Bandung in the Management and Cost Accounting courses. The research method used is descriptive qualitative. This study shows that self-regulated learning if it is divided into 3 indicators, namely planning, implementation, and evaluation is good. As many as 61.35% of students have Self regulated learning seen in the questionnaire responses to the choices strongly agree and agree. Meanwhile 38.65% of students have not implemented Self regulated learning in Management and Cost Accounting courses. A total of 67.45% of students do planning (forethought), 62.20% carry out implementation (performance/valitional control), and 48.77% of students evaluate learning in Management and Cost Accounting courses.